PENGARUH CAREER ADAPT-ABILITIES TERHADAP BURNOUT LEARNING YANG DIMEDIASI ENGAGEMENT LEARNING - Yudhi Purwa Nugraha; Fitri Uswatun Khasanah (SMA Trensains Muhammadiyah Sragen, 2024)
University is an important phase in one's personal and professional development. During this time, students experience a crucial transition from the world of education to the world of work. To survive the challenges of this transition, students need to develop career adapt-abilities to be successful. But there are real problems, which is burnout learning. Research has shown that burnout learning can influence low engagement learning, which in turn leads to low levels of career adapt-abilities. The purpose of the investigation is to find out how career adapt-abilities, engagement learning, and burnout learning are interrelated and affect students' career development. This study is a cross-sectional study using adapted psychological scales. The data were analysed using the mediation regression analysis. The findings revealed that there is a significant relationship between career adapt-abilities, engagement learning, and burnout learning. The present investigation's findings can serve as a basis for the development of career adapt-abilities that focus on self-understanding, skill enhancement, and wisdom in the face of change. An environment that is safe, supportive, and encourages engagement will increase engagement learning.